Efek Anti Diabetes Kombinasi Ekstrak Terpurifikasi Herba Sambiloto (Andrographis paniculata (Burm.f.)Nees) dan Glibenklamid Pada Tikus DM Tipe 2 Defisiensi Insulin - , Iwan Setiawan, Prof. Agung Endro Nugroho, M.Si., Ph.D., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The slow rise to the failure of pancreatic Î²-cell function leads to insulin deficiency. Deficiency of insulin function in people with type 2 diabetes are only relative, not absolute. Insulin deficiency due to reduced growth of pancreatic Î² cell mass, increased apoptosis in the pancreatic Î² cell, regeneration and decreased pancreatic Î²-cell function, genetic disorder with pancreatic Î² cell mitochondria. This study aims to determine the potential of the combination of purified extract of bitter herbs and glibenclamide as an anti-diabetic mice with type 2 diabetes on insulin deficiency. This research was conducted using a randomized complete unidirectional pattern. Stages of the research includes the manufacture of test animals with type 2 diabetes mellitus insulin deficiency, testing the effectiveness of a combination of purified extract of bitter herbs and glibenclamide in lowering blood glucose levels in type 2 diabetes mellitus rat insulin deficiency, histological observation conditions and counting the number of beta cells of the pancreas as well as observations by Immunohistochemical Expression of Insulin (IHC). The results showed that the wistar rats induced by streptozotosin at 3 months has been developed to diabetes mellitus type 2 insulin deficiency with conditions beta cells rat pancreatic degeneration, inflammation and necrosis and followed with as hyperglycemia conditions. Purified extract combination dose of bitter herbs 1303.8 mg/kg and glibenclamide can give the effect of lowering blood glucose levels of diabetic rats type 2 insulin deficiency the most good, it decreased significantly at day 8 and can improve the condition of the pancreas histopathology diabetic rats type 2 through regeneration and inhibit destruction of pancreatic beta cells, increase insulin secretion capacity.